2009
DOI: 10.1152/japplphysiol.00290.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on human skeletal muscle after immobilization and retraining

Abstract: Inactivity is a recognized compounding factor in sarcopenia and muscle weakness in old age. However, while the negative effects of unloading on skeletal muscle in young individuals are well elucidated, only little is known about the consequence of immobilization and the regenerative capacity in elderly individuals. Thus the aim of this study was to examine the effect of aging on changes in muscle contractile properties, specific force, and muscle mass characteristics in 9 old (61-74 yr) and 11 young men (21-27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
372
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(416 citation statements)
references
References 79 publications
32
372
4
8
Order By: Relevance
“…The 25% reduction in knee extension strength following casting was similar to previous observations 15, 27, 30. Muscle weakness following immobilization by a full‐length leg cast was mainly due to the marked decrease in the maximum voluntary force (neurogenic muscle activation) rather than loss of TMV 43.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The 25% reduction in knee extension strength following casting was similar to previous observations 15, 27, 30. Muscle weakness following immobilization by a full‐length leg cast was mainly due to the marked decrease in the maximum voluntary force (neurogenic muscle activation) rather than loss of TMV 43.…”
Section: Discussionsupporting
confidence: 87%
“…In the study by Wall et al .,29 immobilization for 5 days induced muscle loss of ~3.5%, which increased to 8.4% when immobilization was extended to 14 days. While this magnitude of muscle loss can be recovered with little rehabilitation in healthy young men, it is difficult to overcome in elderly patients 14, 15, 16, 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that young men displaying muscle atrophy following 2 weeks of immobilisation regained both quadriceps MVC and muscle volume to reach baseline levels after 4 weeks of resistance training (Suetta et al, 2009). Our study shows that with resistive training performed in the early post-disuse phase recovery from a longer immobilisation period is possible in a shorter recovery timescale.…”
Section: Discussionmentioning
confidence: 96%
“…In a longer ULLS study which lasted 4 weeks and resulted in a 22% decrease in KE strength, muscle torque remained 11% below baseline levels after 4 days of passive recovery, eventually returning to normal 7 weeks following the ULLS period (Berg et al, 1991). Similarly, another study of 2-week immobilization showed that the KE torque could return to pre-ULLS levels within 4 weeks of active recovery (Suetta et al, 2009). The results of this study are noteworthy for they imply that early active recovery may not only improve patient functional status but is likely have a greater impact on quality of life, hereby reducing post-treatment hospitalisation times.…”
Section: Introductionmentioning
confidence: 92%